2007
DOI: 10.1111/j.1440-1681.2007.04623.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Vitamin E and/or Quercetin in Attenuating Chronic Cyclosporine A‐induced Nephrotoxicity in Male Rats

Abstract: 1. The aim of the present study was to investigate the effects of vitamin E and/or quercetin (Q) on renal function, oxygen radical concentrations in the kidney and some anti-oxidant enzyme activities in rats treated with cyclosporine A (CsA). 2. Groups of rats (270 +/- 15 g), on standard rat chow and water, received all their treatments by gavage for either 4 or 8 weeks. Control groups received either olive oil (0.5 mL) or 25% ethanol (0.5 mL) + olive oil (0.5 mL) per day as vehicle. All experimental groups re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 23 publications
3
32
1
Order By: Relevance
“…Several previous studies had suggested that cyclosporine nephrotoxicity may be improved or prevented by antioxidants. [12][13][14][15][16][17] A meta-analysis of clinical trials of CoQ10 for hypertension concluded that CoQ10 had potential for lowering blood pressure in hypertensive patients 18 ; however, in this study, no significant reduction of systolic blood pressure was observed when rCoQ10 was administered with cyclosporine. A possible explanation for this finding is that cyclosporine-induced hypertension may be caused by activation of the intrarenal renin-angiotensin axis, 7 but the renal protective effect of rCoQ10 may be accomplished by another mechanism.…”
Section: Discussioncontrasting
confidence: 60%
“…Several previous studies had suggested that cyclosporine nephrotoxicity may be improved or prevented by antioxidants. [12][13][14][15][16][17] A meta-analysis of clinical trials of CoQ10 for hypertension concluded that CoQ10 had potential for lowering blood pressure in hypertensive patients 18 ; however, in this study, no significant reduction of systolic blood pressure was observed when rCoQ10 was administered with cyclosporine. A possible explanation for this finding is that cyclosporine-induced hypertension may be caused by activation of the intrarenal renin-angiotensin axis, 7 but the renal protective effect of rCoQ10 may be accomplished by another mechanism.…”
Section: Discussioncontrasting
confidence: 60%
“…27 In a study performed on nephrotoxic rats, both vitamin E and quercetin improved renal function to some extent, but it was the combination of the two that lowered the blood urea nitrogen (BUN) and creatinine levels to those seen in HCs. 16 The effect of milk thistle extract and silymarin on kidney SOD level was somehow unexpected in this study. None of the treatments could make a significant increase in SOD level compared to the DC group (Table 2).…”
Section: Prevention Of Diabetic Nephropathy By Milk Thistle Extract Imentioning
confidence: 88%
“…Kidney homogenate was prepared according to the procedure of Zal et al 16 The clear supernatant obtained upon centrifugation was kept at −70°C until used for the estimation of thiobarbituric acid reactive species (TBARS), and for the measurement of the activities of Cu, Zn-superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) enzymes.…”
Section: Preparation Of Kidney Homogenatesmentioning
confidence: 99%
“…RCoQ10 also diminished TGF-beta expression in the proximal renal tubular cells. There are several animal and clinical studies suggesting that antioxidative agents have some preventive effect of CyA nephrotoxicity (7)(8)(9)(10)(11)(12). In 2004, Dlugosz et al reported the benefit of CoQ10 on renal transplant recipients for the first time (13); however, they used ubiquinone, the oxidized form of CoQ10.…”
Section: Discussionmentioning
confidence: 99%